RELEVANSI HAK CUTI SUAMI DALAM UU KETENAGAKERJAAN PASAL 93 AYAT (2) DAN (4) ISTRI DEPRESI PASCA-PERSALINAN - Faruq Alkafi Faruq Alkafi; Ita Rodiah (Yayasan Al-Afif, 2024)
Postpartum depression in women has become a serious concern, especially with its increasing prevalence in various countries. Factors such as lack of attention from partners and emotional instability are often the main causes. This study investigates the limitations of post-partum paternity leave policies in addressing this issue. Qualitative research methods were used to understand this phenomenon through literature search and descriptive analysis. The results highlighted the importance of the husband's role in supporting his wife's mental health postpartum, with effective psychosocial interventions to prevent postpartum depression. However, current paternity leave policies are limited and ineffective. Based on the study, the extension of paid paternity leave and the implementation of paid family leave could have a significant positive impact. This study concludes that holistic efforts, including psychological support and adequate leave policies, are needed to maintain women's mental health postpartum.